Assessing the Causal Relationship between Genetically Determined Inflammatory Cytokines and Parkinson’s Disease Risk: A Bidirectional Two-Sample Mendelian Randomization Study - Hua Xue; Qian Luo; Jiajia Chen; Wenhui Fan (Journal of Immunology Research, 2024)
Background. Observational studies have suggested an association between inflammatory cytokines and Parkinson’s disease (PD). This Mendelian randomization (MR) was conducted to further assess the causal correlations between inflammatory cytokines and PD. Methods. Genetic instruments associated with inflammatory cytokines were extracted from a large summary genome-wide association studies (GWAS) involving 8,293 European participants. Summary-level statistics for PD were obtained from a large-sample GWAS containing 17 studies that involved European participants. Causalities of exposures and outcomes were explored mainly using inverse variance weighted (IVW) method. Results. The IVW method indicated that basic fibroblast growth factor (FGFBasic), interleukin-2 (IL-2), and macrophage migration inhibitory factor (MIF) may be suggestively associated with the risk of PD (OR: 0.71, 95%CI: 0.52–0.96, P = 0.027; OR: 1.18, 95%CI: 1.01–1.38, P = 0.041; and OR: 1.23, 95%CI: 1.04–1.46, P = 0.018). In the reverse direction, monokine induced by interferon gamma (MIG), beta nerve growth factor (bNGF), interleukin-17 (IL-17), and interferon gamma (IFNg) are suggested to be the consequences of PD. Conclusion. Our MR analysis indicated that suggestive associations between circulating levels of FGFBasic, IL-2, and MIF and PD risk. In addition, MIG, bNGF, IL-17, and IFNg are more likely to be involved in the development of downstream PD.